2020
DOI: 10.1508/cytologia.85.301
|View full text |Cite
|
Sign up to set email alerts
|

A Karyomorphological Study on the Genus <i>Muscari</i> Miller Growing in Turkey

Abstract: The chromosome numbers and karyotypes of eight species of the genus Muscari distributed in Turkey were analyzed. These taxa are M. macrocarpum Sweet, M. racemosum Mill., M. aucheri (Boiss.) Baker, M. armeniacum Leichtlin ex Baker, M. sivrihisardaghlarensis Yıldırımlı & B. Selvi, M. discolor Boiss. & Hausskn, M. botryoides (L.) Mill. and M. neglectum Guss. Five of them (M. racemosum, M. aucheri, M. sivrihisardaghlarensis, M. discolor, and M. botryoides) are endemic in Turkey. The chromosome number of all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Eker (2019b) reported that Muscari pamiryigidii is similar to M. armeniacum, M. aucheri, and M. bourgaei, but is easily distinguished from them by its shorter stems, dark brown outer tunics, prominently veined humistrate, and spreading leaves. As with suitable this morphological differences, karyotypes of this endemic species are seen quite comparing to M. armeniacum, M. aucheri and M. bourgaei (Table 4;Karlén 1984b, Demirci Kayıran and Özhatay 2017, Kiran et al 2020b Eker and Yıldırım (2021) reported that M. inundatum is morphologically similar to M. neglectum and M. adilii, but differs mainly by its shouldered fertile flowers with erect to slightly recurved lobes at maturity. Karyotypes of this endemic species are quite distinct from M. neglectum (Table 4; Karlén 1984b, Jafari et al 2008, Demirci Kayıran and Özhatay 2017, Kiran et al 2020b.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Eker (2019b) reported that Muscari pamiryigidii is similar to M. armeniacum, M. aucheri, and M. bourgaei, but is easily distinguished from them by its shorter stems, dark brown outer tunics, prominently veined humistrate, and spreading leaves. As with suitable this morphological differences, karyotypes of this endemic species are seen quite comparing to M. armeniacum, M. aucheri and M. bourgaei (Table 4;Karlén 1984b, Demirci Kayıran and Özhatay 2017, Kiran et al 2020b Eker and Yıldırım (2021) reported that M. inundatum is morphologically similar to M. neglectum and M. adilii, but differs mainly by its shouldered fertile flowers with erect to slightly recurved lobes at maturity. Karyotypes of this endemic species are quite distinct from M. neglectum (Table 4; Karlén 1984b, Jafari et al 2008, Demirci Kayıran and Özhatay 2017, Kiran et al 2020b.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, he reported that the satellites are situated on the short arms of the second pair. Kiran et al (2020b) reported the karyotype of M. botryoides as 14m+2sm+2sm SAT . Therefore, we can interpret the karyotypes of this endemic species are partly similar to M. armeniacum in terms of having 7m and 2sm chromosomes (Table 4 for M. armeniacum ;Karlén 1984a, b, Demirci Kayıran and Özhatay 2017, Kiran et al 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Garbari & Greuter (1970) used caryology to argue for their classification, but based on a relatively small species sample (Speta, 1982), with only marginal overlap with our sampling. Current karyomorphological studies (Kiran & al., 2020) may still expand our understanding of the lineages. Seed morphology has also been used in Asparagaceae (Pfosser & al., 2003) in general and in Muscari in Turkey (Eroğlu & al., 2021), but without providing useful insights into the phylogenetic relationship in Muscari .…”
Section: Discussionmentioning
confidence: 99%
“…Muscari türlerinin çoğunluğu diploid (2n=2x=18) iken, birkaç popülasyon poliploiddir (Stuart 1970;Karlén 1984;Dalgıç 1991;Johnson 1994;Özhatay & Johnson 1996;Johnson & Brandham 1997;Demirci Kayıran & Özhatay 2017;Kıran vd. 2020a;2020b;Bozkurt 2020).…”
unclassified